Study on the Optimization of Filling Ratio and Strength Variation Characteristics of Cemented Backfills Containing Fly Ash - Chang, Baomeng; Du, Cuifeng; Chu, Xiaofeng; Zhang, Long (Frontiers in Materials, 2021)
The fly ash for underground filling can effectively utilize solid waste, improve the strength of the backfill and reduce the cost, thus creating good social and economic benefits. Relying on the filling requirements of a gold mine in Jilin, this paper carried out the filling ratio experiments containing fly ash, and analyzed the reasons for the variation of the backfill strength based on the hydration characteristics of cement and fly ash and scanning electron microscope. The results show that: fly ash has an overall effect on the strength of the backfill, and the strength development is mainly concentrated in the period of 28d-56d; when the filling slurry contains tailings, the excessive amount of fly ash is likely to cause a large number of fine particles to obstruct the hydration of cementitious materials; when the concentration of the filling slurry is 74%, the cement content is 5%, the mass ratio of waste rock-tailings-fly ash is 6:2:3, and the CaO content is 6:3, the strength of the backfill is significantly higher than the current strength of the backfill of the mine, and the cost can be saved by RMB 0.56 per cubic meter; the strength characteristics of the backfill mainly depend on the pore structure, when the filling slurry is better matched, the cement and fly ash hydration generates a large number of C-S-H gel particles, which wraps the aggregate to form a dense structure with less pore structure, and the strength of the backfill increases; the strength variation process of backfill containing cement and fly ash is divided into cement hydration period, fly ash infiltration period, and slurry hardening period. To enhance the strength of the backfill, it is necessary to determine the appropriate cementitious material ratio to maximize the excitation of fly ash hydration during the fly ash infiltration period, and the hydration produces a gel structure with an excellent aggregate ratio. In addition, the slurry hardening reduces the porosity of the backfill. The results can provide basic data and theoretical guidance for further promotion and application of fly ash in mine filling.